2014
DOI: 10.1603/me13236
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal Properties of the Essential Oil FromZanthoxylum caribaeumAgainstRhipicephalus microplus

Abstract: Zanthoxylum caribaeum Lamarck (Rutaceae) is plant species with a variety of medical applications, including insecticidal activity. This study determined the bioacaricidal activity of the essential oil from Z. caribaeum leaves against engorged Rhipicephalus (Boophilus) microplus (Canestrini, 1887) females using the adult immersion test. For this purpose, three serial concentrations (5.0, 2.5, and 1.25%, vol:vol, in 1% dimetilsulfoxide) of the essential oil were used. Essential oil 5% caused 65% mortality on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
0
11
1
2
Order By: Relevance
“…The toxic activity of plant extracts of the genus Zanthoxylum against arthropods is well known, both to insect (MOUSSAVI et al, 2015) as larvae of the R. microplus tick (SANTOS et al, 2013). In relation to the species Z. caribauem, a high toxicity of the leaf essential oil on the R. microplus tick was reported, as mortality of 97% (NOGUEIRA et al, 2014a), however, this is the first study in which the toxicity of Z. caribaeum to the D. gallinae mite. So, phytochemical composition study is necessary and recommended.…”
Section: Acaricidal Activitymentioning
confidence: 84%
See 1 more Smart Citation
“…The toxic activity of plant extracts of the genus Zanthoxylum against arthropods is well known, both to insect (MOUSSAVI et al, 2015) as larvae of the R. microplus tick (SANTOS et al, 2013). In relation to the species Z. caribauem, a high toxicity of the leaf essential oil on the R. microplus tick was reported, as mortality of 97% (NOGUEIRA et al, 2014a), however, this is the first study in which the toxicity of Z. caribaeum to the D. gallinae mite. So, phytochemical composition study is necessary and recommended.…”
Section: Acaricidal Activitymentioning
confidence: 84%
“…In this context, the species Zanthoxylum caribaeum L. (Rutaceae), despite the scarcity of studies in the literature, is notable for the presence of antimicrobial activity of its extracts and its essential oil against Salmonella serotypes of poultry origin (SOUZA et al, 2017), as well as for Staphylococcus aureus and Escherichia coli (ORDAZ PICHARDO et al, 2014). Its toxicity as an acaricide for Rhipicephalus microplus (Canestrini) (Acari: Ixodidae) (NOGUEIRA et al, 2014a) and as an insecticide for Rhodnius prolixus (Stal) (Hemiptera: Reduviidae) (NOGUEIRA et al, 2014b) has also been confirmed.…”
Section: Introductionmentioning
confidence: 91%
“…Diversos OEs das espécies exibidas neste estudo mostraram eficácia significativamente maior, quando em comparação com outros OEs testados, demonstrando 100% de letalidade contra R. microplus em um ou mais dos ensaios realizados (Tabela 1). São elas: Drimys brasiliensis (RIBEIRO et al, 2008), Tetradenia riparia (GAZIM et al, 2011), Lippia sidoides (GOMES et al, 2012), Tagetes minuta (GARCIA et al, 2012), Lippia triplinervis (LAGE et al, 2013), Syzygium aromaticum (MELLO et al, 2014), Zanthoxylum caribaeum (NOGUEIRA et al, 2014), Chrysopogon zizanioides (CAMPOS et al, 2015), Curcuma longa (CHAGAS et al, 2016), Zingiber officinale (CHAGAS et al, 2016), Lippia alba, L. gracilis, L. origanoides (CHAGAS et al, 2016), Cymbopogon martinii (PAZINATO et al, 2016), Cedrus atlântica (PAZINATO et al, 2016), C. citratus (PAZINATO et al, 2016;SILVA et al, 2020), Cuminum cyminum (VILLARREAL et al, 2017), Hesperozygis myrtoides (CASTILHO et al, 2017), Citrus limonum (VINTURELLE et al, 2017), Mesosphaerum suaveolens (CASTRO et al, 2018), Alpinia zerumbet (CASTRO et al, 2018), Croton conduplicatus, C. pulegiodoruse C. grewioides (CASTRO et al, 2019). Dos OEs utilizados, os três principais componentes majoritários identificados em maior concentração na análise quantitativa foram metil chavicol (95,38% e 83,59% em C. grewioides), sesquirosefurano (92,2% em C. grewioides) e geraniol (81,4% em C. martinii), nos respectivos estudos de Castro et al (2019), Figueiredo et al (2017) e Chagas et al (2012).…”
Section: óLeos Essenciais Com Atividade Acaricida Componentes Majoritários E Moléculas Isoladasunclassified
“…A análise do óleo essencial obtido a partir das folhas de Z. caribaeum forneceu os seguintes componentes: D-limoneno (12), linalool (13), espatulenol (14), β-cariofileno (16), α-muurolol (22), α-cadinol (23), copaeno (24), β-Bourboneno (25), n-hexanol (32), α-tujeno (33), sabineno (34), α-pineno (35), β-mirceno (36), β-E-ocimeno (37), α-felandreno 38 (Nogueira et al 2014b, Souza et al 2017, Feder et al 2019.…”
Section: Zanthoxylum Caribaeum Lamunclassified